Synthesis and characterization of divinylbenzene-based cyanate resin and its quartz fiber-reinforced composite. (December 2020) - Wei, Yunzhao; Shen, Dongliang; Wu, Jianwei; Zhao, Yuyu; Wang, Guan; Fu, Gang; Kuang, Hong
Cyanate ester (CE) resins are important polymeric materials with excellent dielectric properties, low moisture absorption, and good heat resistance, which have shown great superiority for use in electronic and aerospace industries. In this article, a novel CE resin was designed and synthesized from divinylbenzene. The proposed structures were characterized with Fourier transform infrared spectroscopy, gel permeation chromatography, and mass spectrometry. The chemical reaction activity, heat resistance, dielectric properties, and water adsorption of the synthesized CE derived from divinylbenzene (DVBCy) were examined and compared with the traditional bisphenol A and bisphenol M (4, 4′-[1, 3-phenylenebis(1-methyl-ethylidene)]bisphenol)-based CE. The DVBCy resin exhibits a glass transition temperature ( T g ) of 162.7°C, a dielectric constant of 2.61, a dielectric loss tangent angle of 0.0035 at about 10 GHz, and a lower water absorption of 0.77%. Compared with the bisphenol M type CE, DVBCy resin provides slightly superior dielectric properties, higher mechanical properties, more favorable process technology for prepreg construction, and lower costing. The DVBCy blend resin modified with bisphenol A-based CE and core–shell particles possesses suitable rheological properties, and the corresponding quartz fiber-reinforced composite exhibits excellent mechanical as well as dielectric properties.